(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine the implementation of the E-Toll System in Makassar City. E-Toll was an electronic payment system used electronic money. Based on this, researcher encouraged to explain the Implementation of the E-Toll System in Makassar City. The number of informants in this study was 4 people. This study used qualitative research with a type of phenomenological research that emphasized the subjectivity of human life experiences. Data collection techniques used the method of observation, interviews and documentation. Data analysis used interactive analysis models. The results showed that the implementation of the E-Toll System in Makassar City had not been fully implemented optimally in accordance with its objectives, this was seen from the indicators namely (1) input, (2) process, (3) output, (4) benefits, and (5) ) outcome. In the Process indicators there were still many problems, such as the existence of the community or toll road users who did not yet have an E-Toll card to make payments manually, because it was still lack of information and information from related parties that the importance of using the E-Toll card so that the public understood and used the E-toll Card system.